Monoamine structure and its effect on fully reacted substructures to synergistically toughen epoxy amine networks via topological control - Nguyen Thao Phan; Houlei Gan; David Szmalko; Claudia Creighton; Cara M. Doherty; Durga Acharya; Daniel J. Eyckens; Russell J. Varley (Chemical Engineering Journal, 2026)

Parallel concepts and future opportunities across the biological control and invasion sciences - Ross N. Cuthbert; Nompumelelo Baso; Tressia Chikodza; Candice Coombes; Jane Doherty; Michael Githae; Tamzin C. Griffith; Marco R. Hernandez; Karla M. Jaschke; Michael D. Jukes; David Kinsler; Hugh J. MacIsaac; et al. (Journal of Environmental Management, 2026)

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Animal-borne sensors reveal high human impact on soundscapes near a critical sea turtle nesting beach - Francesco Garzon; Pierre Didier Agamboue; Jack A. Boyle; Philip D. Doherty; Angela Formia; Brendan J. Godley; Lucy A. Hawkes; David A. Mann; Sara M. Maxwell; Richard J. Parnell; Stephen K. Pikesley; Guy-Phillipe Sounguet; et al. (Biological Conservation, 2024)

Ozone at Mace Head, Ireland from 1987 to 2021: Declining baselines, phase-out of European regional pollution, COVID-19 impacts - Richard G. Derwent; David D. Parrish; Alistair J. Manning; T. Gerard Spain; Peter G. Simmonds; Simon O'Doherty (Atmospheric Environment, 2024)

Social and structural vulnerabilities: Associations with disaster readiness - Smitha Rao; Fiona C. Doherty; Samantha Teixeira; David T. Takeuchi; Shanta Pandey (Global Environmental Change, 2023)

Threat-abatement framework confirms habitat retention and invasive species management are critical to conserve Australia's threatened species - Stephen G. Kearney; James E.M. Watson; April E. Reside; Diana O. Fisher; Martine Maron; Tim S. Doherty; Sarah M. Legge; John C.Z. Woinarski; Stephen T. Garnett; Brendan A. Wintle; Euan G. Ritchie; Don A. Driscoll; et al. (Biological Conservation, 2023)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Ethnicity, socioeconomic status, income inequality, and colorectal cancer outcomes: evidence from the 4C2 collaboration - Cathy J. Bradley; Amy Anderson-Mellies; Evelinn A. Borrayo; Jennifer Anne Doherty; Omar A. Escontrías; David O. Garcia; Shiraz I. Mishra; Andrew L. Sussman; Cynthia A. Thomson; David W. Wetter; Linda S. Cook (Cancer Causes & Control, 2022)

Validation of Tidal Stream Turbine Wake Predictions and Analysis of Wake Recovery Mechanism - Sanchit Salunkhe; Oumnia El Fajri; Shanti Bhushan; David Thompson; Daphne O’Doherty; Tim O’Doherty; Allan Mason-Jones (Journal of Marine Science and Engineering, 2019)
This paper documents the predictive capability of rotating blade-resolved unsteady Reynolds averaged Navier-Stokes (URANS) and Improved Delayed Detached Eddy Simulation (IDDES) computations for tidal stream turbine performance and intermediate wake characteristics. Ansys/Fluent and OpenFOAM simulations are performed using mixed-cell, unstructured grids consisting of up to 11 million cells. The thrust, power and intermediate wake predictions compare reasonably well within 10% of the experimental data. For the wake predictions, OpenFOAM performs better than Ansys/Fluent, and IDDES better than URANS when the resolved turbulence is triggered. The primary limitation of the simulations is under prediction of the wake diffusion towards the turbine axis, which in return is related to the prediction of turbulence in the tip-vortex shear layer. The shear-layer involves anisotropic turbulent structures; thus, hybrid RANS/LES models, such as IDDES, are preferred over URANS. Unfortunately, IDDES fails to accurately predict the resolved turbulence in the near-wake region due to the modeled stress depletion issue.

Genetic modifiers of radon-induced lung cancer risk: a genome-wide interaction study in former uranium miners - Albert Rosenberger; Rayjean J. Hung; David C. Christiani; Neil E. Caporaso; Geoffrey Liu; Stig E. Bojesen; Loic Le Marchand; Ch. A. Haiman; Demetrios Albanes; Melinda C. Aldrich; Adonina Tardon; G. Fernández-Tardón; et al. (International Archives of Occupational and Environmental Health, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

The development of an in vitro Pig-a assay in L5178Y cells - Rhiannon David; Emily Talbot; Bethany Allen; Amy Wilson; Usman Arshad; Ann Doherty (Archives of Toxicology, 2018)

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

Public concerns regarding the storage and secondary uses of residual newborn bloodspots: an analysis of print media, legal cases, and public engagement activities - Shannon Cunningham; Kieran C. O’Doherty; Karine Sénécal; David Secko; Denise Avard (Journal of Community Genetics, 2015)

Coupled Chemical Shrinkage and Consolidation: Some Benchmark Solutions - David Muir Wood; James Peter Doherty (Transport in Porous Media, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Biomaterial-Based Vaccine Induces Regression of Established Intracranial Glioma in Rats - Omar A. Ali; Ed Doherty; William J. Bell; Tracie Fradet; Jebecka Hudak; Marie-Therese Laliberte; David J. Mooney; Dwaine F. Emerich (Pharmaceutical Research, 2011)

Population structure and genetic diversity of greater sage-grouse (Centrocercus urophasianus) in fragmented landscapes at the northern edge of their range - Krista L. Bush; Christopher K. Dyte; Brendan J. Moynahan; Cameron L. Aldridge; Heather S. Sauls; Angela M. Battazzo; Brett L. Walker; Kevin E. Doherty; Jason Tack; John Carlson; Dale Eslinger; Joel Nicholson; et al. (Conservation Genetics, 2011)

“Fit-for-Purpose” Method Validation and Application of a Biomarker (C-terminal Telopeptides of Type 1 Collagen) in Denosumab Clinical Studies - Jin Wang; Jean Lee; Daniel Burns; David Doherty; Laura Brunner; Mark Peterson; Binodh DeSilva (The AAPS Journal, 2009)

ABOVEGROUND AND BELOWGROUND EFFECTS OF SINGLE‐TREE REMOVALS IN NEW ZEALAND RAIN FOREST - David A. Wardle; Susan K. Wiser; Robert B. Allen; James E. Doherty; Karen I. Bonner; Wendy M. Williamson (Ecology, 2008)
There has been considerable recent interest in how human‐induced species loss affects community and ecosystem properties. These effects are particularly apparent when a commercially valuable species is harvested from an ecosystem, such as occurs through single‐tree harvesting or selective logging of desired timber species in natural forests. In New Zealand mixed‐species rain forests, single‐tree harvesting of the emergent gymnosperm Dacrydium cupressinum, or rimu, has been widespread. This harvesting has been contentious in part because of possible ecological impacts of Dacrydium removal on the remainder of the forest, but many of these effects remain unexplored. We identified an area where an unintended 40‐year “removal experiment” had been set up that involved selective extraction of individual Dacrydium trees. We measured aboveground and belowground variables at set distances from both individual live trees and stumps of trees harvested 40 years ago. Live trees had effects both above and below ground by affecting diversity and cover of several components of the vegetation (usually negatively), promoting soil C sequestration, enhancing ratios of soil C:P and N:P, and affecting community structure of soil microflora. These effects extended to 8 m from the tree base and were likely caused by poor‐quality litter and humus produced by the trees. Measurements for the stumps revealed strong legacy effects of prior presence of trees on some properties (e.g., cover by understory herbs and ferns, soil C sequestration, soil C:P and N:P ratios), but not others (e.g., soil fungal biomass, soil N concentration). These results suggest that the legacy of prior presence of Dacrydium may remain for several decades or centuries, and certainly well over 40 years. They also demonstrate that, while large Dacrydium individuals (and their removal) may have important effects in their immediate proximity, within a forest, these effects should only be important in localized patches containing high densities of large trees. Finally, this study emphasizes that deliberate extraction of a particular tree species from a forest can exert influences both above and below ground if the removed species has a different functional role than that of the other plant species present.

Linkage mapping of the locus for inherited ovine arthrogryposis (IOA) to sheep Chromosome 5 - Angela M. Murphy; David E. MacHugh; Stephen D.E. Park; Erik Scraggs; Chris S. Haley; David J. Lynn; Maurice P. Boland; Michael L. Doherty (Mammalian Genome, 2007)

Uptake and Persistence of the Vertebrate Pesticide, Sodium Monofluoroacetate (Compound 1080), in Plants of Cultural Importance - Shaun C. Ogilvie; James M. Ataria; James Waiwai; James E. Doherty; Michelle Lambert; Neuton Lambert; David King (Ecotoxicology, 2006)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)